EcoLab: A Tool for Modeling and Analyzing Potential Species Distribution - Simões, Ane C.; Martins, Aline C.; Dorini, Leyza B.; Gomes-Jr, Luiz (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2026.249386, 2026)
Species distribution modeling (SDM) is widely used in ecological research; however, its traditional implementation in R still presents limitations, such as the difficulty of selecting the appropriate packages and the absence of biotic variables (data on species that interact with the target species). Given this context, this work presents the development of an application that automates and integrates all stages of building an SDM, encompassing steps from obtaining occurrence data to extracting environmental variables, modeling, and evaluating results.